Decomposition of Energy Consumption and Decoupling Analysis in the Indonesian Industry: An Analysis of Green Industry - Zaekhan, Zaekhan; Nachrowi, Nachrowi Djalal; Lubis, Andi Fahmi; Soetjipto, Widyono; Rosita, Tita; Widharosa, Nona (International Journal of Energy Economics and Policy, 2019)
This study aims to identify ways that efficiently reduce the energy consumption of the industrial sector. We use the Logarithmic Mean Divisia index (LMDI) method to measure the impact of the various driving forces of energy consumption during the period 2010-2014. We then apply the index decoupling to analyze the correlation between energy consumption and industrial growth. The findings indicate that industrial growth is a major driver of energy consumption, while reductions in energy intensity and industrial structure play an important role in limiting energy consumption. In addition, energy consumption and energy intensity follow different patterns in each sub-sector; we therefore conclude that the application of different sub-sector policies is preferred over global policies. Globally, decoupling has not been identified during the period 2010-2014, however, decoupling occurs for more detailed year periods. Keywords: Energy consumption; LMDI; Decoupling. JEL Classifications: L52, L60, O25, Q43. DOI: https://doi.org/10.32479/ijeep.8027